Rapid product development. - Chong, Hung Hiong. (2009)
General industry trend is toward rapidly shrinking product development cycle times with accelerating rates of new-product introductions. In a highly competitive environment where market response time becoming faster and consumer expectations for product quality and variety continue to expand, rapid product development becomes a critical success factor towards a sustainable competitive advantage.